2021
DOI: 10.3390/risks9050092
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management in the Management Control System in Polish Local Government Units—Assumptions and Practice

Abstract: The issues related to management control and risk management are related not only to the safe operation of a given organization, but also contribute to ensuring the continuity of its operations. The main purpose of this article is to present the general principles of the organization of the management control and risk management system and to check the knowledge of its essence and principles by the employees of local government units. In the empirical part of the article, the method of desk research was used, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…ISO 31000:2018 also has been proven by previous studies to be crucial in making a decision (Blokland & Reniers, 2021; Buganova et al, 2021). In terms of identifying potential risks, some studies also confirmed that ISO 31000:2018 was able to help the company identify the upcoming risks that it has to face (Mormul, 2021;Ruiz-Canela López, 2021). Since ISO 31000:2018 brings benefits to the company, this ERM is believed to be effective in reducing company losses (Ahn et al, 2020;Tiganoaia et al, 2019).…”
Section: Reduce Lossesmentioning
confidence: 85%
“…ISO 31000:2018 also has been proven by previous studies to be crucial in making a decision (Blokland & Reniers, 2021; Buganova et al, 2021). In terms of identifying potential risks, some studies also confirmed that ISO 31000:2018 was able to help the company identify the upcoming risks that it has to face (Mormul, 2021;Ruiz-Canela López, 2021). Since ISO 31000:2018 brings benefits to the company, this ERM is believed to be effective in reducing company losses (Ahn et al, 2020;Tiganoaia et al, 2019).…”
Section: Reduce Lossesmentioning
confidence: 85%
“…Few studies in the literature, therefore, have focused on the practical implementation of risk management in municipalities. By practical implementation we mean learning procedures and techniques integrated with the management control system (Mormul 2021). Mormul (2021) investigated how RM integrated into the management control system of Local Government Units, concluding that "the understanding of the essence and principles of management control system and risk management by employees is incomplete".…”
Section: The Role Of the Municipality In The Italian Context And Risk...mentioning
confidence: 99%
“…By practical implementation we mean learning procedures and techniques integrated with the management control system (Mormul 2021). Mormul (2021) investigated how RM integrated into the management control system of Local Government Units, concluding that "the understanding of the essence and principles of management control system and risk management by employees is incomplete". For these reasons, a specific focus on the topic proposed is necessary.…”
Section: The Role Of the Municipality In The Italian Context And Risk...mentioning
confidence: 99%
“…A concept for measuring project maturity was created by Mormul (2021) in the form of a weighted average of values (i.e., an average probability of the planned factors: 0.00-0.20, 0.21-0.40, 0.41-0.60, 0.61-0.80, and 0.81-1.00) scaled according to their importance (number of respondents choosing the correct answer). In addition, the indicator value of 1.0 implies that the surveyed companies rate their project maturity as perfect (fully mature organization), while 0.0 means that an organization is not project mature at all.…”
Section: Project Management Maturity Measuresmentioning
confidence: 99%